Operational Modal Analysis for Estimating the Dynamic Properties of a Stadium Structure during a Football Game - Bart Peeters; Herman Van der Auweraer; Frederik Vanhollebeke; Patrick Guillaume (Shock and Vibration)
During a football game, the ambient vibrations at the roof of a football stadium were recorded. A very large data set consisting of 4 hours of data, sampled at 80 Hz, is available. By a data reduction procedure, the complete data set could be analysed at once in a very short time. The data set was also split in shorter segments corresponding to certain events before, during and after the game to investigate the influence of varying operational conditions on the dynamic properties.